2008
DOI: 10.1111/j.1523-5378.2008.00606.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori‐Pulsed Dendritic Cells Induce H. pylori‐Specific Immunity in Mice

Abstract: Background-The growing concern over the emergence of antibiotic-resistant Helicobacter pylori infection is propelling the development of an efficacious vaccine to control this highly adaptive organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…Gastric quantitative PCR analyses revealed an increase in Foxp3 mRNA expression and a decrease in IL-17/Foxp3 mRNA ratio in HP-DC transferred compared with PBS-DC transferred mice (Figure 5 D and E ). No significant difference in H pylori colonization or gastritis was detected (Supplementary Figure 2), possibly due to the concurrent increase in H pylori –specific immunity induced by HP-DCs 17. These data indicate that HP-DC induces a Treg-skewed response.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Gastric quantitative PCR analyses revealed an increase in Foxp3 mRNA expression and a decrease in IL-17/Foxp3 mRNA ratio in HP-DC transferred compared with PBS-DC transferred mice (Figure 5 D and E ). No significant difference in H pylori colonization or gastritis was detected (Supplementary Figure 2), possibly due to the concurrent increase in H pylori –specific immunity induced by HP-DCs 17. These data indicate that HP-DC induces a Treg-skewed response.…”
Section: Resultsmentioning
confidence: 75%
“…DCs isolated from H felis infected stomach also showed increased costimulatory molecules 16. We and Otsu et al previously reported H pylori -pulsed DCs were able to augment anti- H pylori immunity, but neither study was able to completely eradicate H pylori 17, 38. In this study, HP-DC induce both H pylori -specific Treg and Th1/Th17 responses in vivo but the net results is a Treg skewed response; this is a possible explanation for the inability of DC vaccine to completely eradicate H pylori .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Specifically, cells were first treated with low dose E. coli LPS, allowed to rest overnight, and then stimulated with H. pylori sonicate. H. pylori sonicate was used due to its distinct immunomodulatory capabilities, and to provide contrasting H. pylori LPS stimulation to the initial tolerizing stimulus of E. coli LPS [3135]. Despite exposure to different components, BM-DC tolerance was maintained when assayed for TNF-α and IL-10.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of Th1 immunity against H. pylori is well established [30-32]. Thus, the ability of H.…”
Section: Discussionmentioning
confidence: 99%